Efikasi Diri, Kepatuhan, dan Kualitas Hidup Pasien Diabetes Melitus Tipe 2 (Self Efficacy, Adherence, and Quality of Life of Patients with Type 2 Diabetes) - Handono Fatkhur Rahman; Yulia Yulia; Lestari Sukmarini (Pustaka Kesehatan, 2017)
Self-efficacy and adherence are important factor in improving the quality of life of patients with type 2 diabetes. This study aimed to determine the relationship between self-efficacy and adherence to the quality of life of patients with type 2 diabetes mellitus. This study was a cross-sectional, with sample of 125 patients with type 2 diabetes mellitus. The Diabetes Management Self-Efficacy (DMSES), the Diabetes Activities Questionare (TDAQ), and the Diabetes Quality of Life (DQOL) were employed as instruments. The results showed that self-efficacy (0.0005), and adherence (0.0005) were significantly associated with quality of life and the most dominant variable is adherence. Multivariate test results indicate that the variable self-efficacy, adherence, depression, and education level determines quality of life of diabetic patients. This study suggestion the need for nursing assessment and interventions that focus on the self-efficacy and adherence diabetes mellitus patient. Keywords: self efficacy, adherence, quality of life, diabetes type 2